Multifaceted Roles for Macrophages in Prostate Cancer Skeletal Metastasis - Lo, Chen Hao; Lynch, Conor C. (Frontiers in Endocrinology, 2018)
Bone-metastatic prostate cancer is common in men with recurrent castrate-resistant disease. To date, therapeutic focus has largely revolved around androgen deprivation therapy (ADT) and chemotherapy. While second generation ADTs and combination ADT/chemotherapy approaches have been successful in extending overall survival, the disease remains incurable. It is clear that molecular and cellular components of the cancer-bone microenvironment contribute to the disease progression and potentially to the emergence of therapy resistance. In bone, metastatic prostate cancer cells manipulate bone-forming osteoblasts and bone-resorbing osteoclasts to produce growth and survival factors. While osteoclast-targeted therapies such as bisphosphonates have improved quality of life, emerging data has defined important roles for additional cells of the bone microenvironment including macrophages and T cells. Disappointingly, early clinical trials with checkpoint blockade inhibitors geared at promoting cytotoxic T cell response have not proved as promising for prostate cancer compared to other solid malignancies. Macrophages, including bone-resident osteomacs, are a major component of the bone marrow and play key roles in coordinating normal bone remodeling and injury repair. The role for anti-inflammatory macrophages in the progression of primary prostate cancer is well established yet relatively little is known about macrophages in the context of bone-metastatic prostate cancer. The focus of the current review is to summarize our knowledge of macrophage contribution to normal bone remodeling and prostate-to-bone metastasis, while also considering the impact of standard of care and targeted therapies on macrophage behavior in the tumor-bone microenvironment.